Temporal and spatial changes in golden eagle reproduction in relation to increased off highway vehicle activity - Karen Steenhof; Jessi L. Brown; Michael N. Kochert (Wildlife Society Bulletin)
ABSTRACT We used >40 years of data on golden eagles (Aquila chrysaetos) nesting in southwestern Idaho, USA, to assess whether the proportion of territories and pairs producing young has changed over time, and whether territories in areas where off highway vehicle (OHV) use has increased significantly were less likely to be productive than those in areas that continued to have little or no motorized recreation. The proportion of territories that produced young was similar across southwestern Idaho from the late 1960s to 1999. After a dramatic increase in OHV use from 1999 to 2009, occupancy and success of territories in close proximity to recreational trails and parking areas declined, and the proportion of these territories producing young differed significantly from territories not impacted by OHVs. We could not pinpoint which types of motorized activity are most disturbing, nor could we identify disturbance thresholds at which eagles abandon their eggs, their young, and finally their territory. Timing, proximity, duration, and frequency of disturbance could all play a role. © 2014 The Wildlife Society.